2019
DOI: 10.1007/s12665-019-8542-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequential soil washing with mixed biosurfactants is suitable for simultaneous removal of multi-metals from soils with different properties, pollution levels and ages

Abstract: In this study, plant (SAP, TAN) and microbial (RAM) biosurfactants were applied to two soils, in single or sequential soil washing. Soil 1 was moderately acidic, with higher content of organic matter and HMs (Cd, Cu, Ni, Pb and Zn), and was aged for 24 months. Soil 2 was alkaline, with lower content of organic matter and HMs, and was aged for 1 month. The stability of the HMs (as I R), except for Pb, was higher in soil 1 than in soil 2, but the rankings of HM stability were similar: Cu > Ni ≈ Pb > Zn > Cd (soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This is because, in the soil, the Cu concentration was higher than that of Pb, and there was strong competition between Cu and Pb for the carboxylic groups in saponin [ 15 ]. As for tannic acid, it is a polyphenol, i.e., an organic ligand with a high molecular weight and numerous phenolic groups that can form complexes with metals [ 42 , 44 ]. In soil, tannic acid can react with Fe, decomposing Fe oxides and facilitating release of metals bound to oxides [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because, in the soil, the Cu concentration was higher than that of Pb, and there was strong competition between Cu and Pb for the carboxylic groups in saponin [ 15 ]. As for tannic acid, it is a polyphenol, i.e., an organic ligand with a high molecular weight and numerous phenolic groups that can form complexes with metals [ 42 , 44 ]. In soil, tannic acid can react with Fe, decomposing Fe oxides and facilitating release of metals bound to oxides [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the optimum concentration of tannic acid for simultaneous removal of multi-metals from soil is ≥20 g TOC/L [ 20 ]. At higher concentrations, tannic acid is more acidic due to the presence of more acidic phenolic groups, which facilitate removal of metals like Pb [ 15 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the metal stability (based on IR) in soils after washing were conducted by Gusiatin et al 54 . The authors have found that application of different biosurfactants as WAs (saponin, tannic acid, rhamnolipids) significantly increased the stability of Cd, Cu, Ni, Pb and Zn (based on the IR) in spiked soil.…”
Section: Suitability Of Different Environmental Indices For Assessmenmentioning
confidence: 99%
“…When Fe (II) is complexed to TA, it is unable to participate in Fenton-like processes and to mediate the formation of hydroxyl radicals [ 24 ]. There is little information on the use of TA in soil remediation and, moreover, only concerning soil washing [ 21 , 25 , 26 ] and phytoremediation [ 27 ], not soil flushing.…”
Section: Introductionmentioning
confidence: 99%